Efficacy of Topical 1% Oxiconazole Cream in the Treatment of Dermatophytosis - Islam, Md Tawhidul; Akhter, Shamima; Khondker, Lubna; Khan, Md Shirajul Islam; Siddiqua, Ayesha (Journal of Enam Medical College, 2014)
Background: Dermatophytosis is a geographically widespread group of fungal infections. Tinea corporis and tinea cruris are the most common dermatophytoses in Bangladesh. Oxiconazole has recently been introduced in Bangladesh in the treatment of dermatophytoses. Objective: To evaluate the efficacy of topical 1% oxiconazole cream once daily in the treatment of tinea corporis and tinea cruris. Materials and Methods: A clinical trial was carried out in the department of Dermatology and Venereology, Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet on 81 patients with tinea corporis and/or tinea cruris. The patients were instructed to apply 1% oxiconazole cream once daily for 2 weeks with clinical assessment made at weekly intervals during treatment period. Results: The mean age of the patients was 32.5 ± 10.5 years, with tinea corporis in 47 (58.0%) patients and tinea cruris in 34 (42.0%). The mean clinical assessment score declined from 6.6 ± 1.3 at baseline to 3.9 ± 1.2 at week 1, 0.9 ± 1.3 at week 2 and 0.7 ± 1.1 at week 4. Reduction of clinical assessment score from baseline to end of the treatment period was statistically significant (p<0.001). The improvement of clinical score was from baseline to 41.6% at week 1, 89.3% at week 2 and 91.5% at week 4. Improvement of clinical score from baseline to end of the treatment period was statistically significant (p<0.001). Global response was clear in 55 (67.9%) patients, good in 25 (30.9%) patients and fair in 1(1.2%) patient. Clinical efficacy was cure in 55 (67.9%) patients, improvement in 25 (30.9%) and failure in 1(1.2%) patient. Conclusion: Once daily topical administration of oxiconazole cream is highly effective in the treatment of superficial fungal infections of the skin. DOI: http://dx.doi.org/10.3329/jemc.v4i2.19479 J Enam Med Col 2014; 4(2): 89-93